2015
DOI: 10.3892/ijo.2015.3154
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction induces EMT through the TGF-β/Smad/Snail signaling pathway in Hep3B hepatocellular carcinoma cells

Abstract: Mitochondrial dysfunction has been found to be associated with various pathological conditions, particularly cancer. However, the mechanisms underlying tumor malignancy induced by mitochondrial dysfunction are not fully understood. In the present study, the effects of mitochondrial dysfunction on epithelial-mesenchymal transition (EMT), were investigated using mitochondrial-depleted ρ(0) cells derived from the Hep3B hepatocarcinoma cell line. The Hep3B/ρ(0) cells displayed the EMT phenotype with more aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…For example, OXPHOS dysfunction has been reported to be involved in cell migration, invasion and metastasis (32). In addition, it was recently demonstrated that mitochondrial dysfunction promotes EMT through the transforming growth factor (TGF)-β/Smad/Snail signaling pathway by activating c-Jun/activator protein-1 in hepatocellular carcinoma cells (33). Another study also demonstrated that mitochondrial dysfunction following TGFβ-1 exposure induces acquisition of a mesenchymal morphology and the transfer from an epithelial to a mesenchymal phenotype in pancreatic cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, OXPHOS dysfunction has been reported to be involved in cell migration, invasion and metastasis (32). In addition, it was recently demonstrated that mitochondrial dysfunction promotes EMT through the transforming growth factor (TGF)-β/Smad/Snail signaling pathway by activating c-Jun/activator protein-1 in hepatocellular carcinoma cells (33). Another study also demonstrated that mitochondrial dysfunction following TGFβ-1 exposure induces acquisition of a mesenchymal morphology and the transfer from an epithelial to a mesenchymal phenotype in pancreatic cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…The EMT process can be induced in several cancer cell lines ( 69 71 ), usually by TGF-β1 addition or hypoxia, the most common inducers ( 72 ).…”
Section: Epithelial-to-mesenchymal Transition: Differences Between Nomentioning
confidence: 99%
“…Previous work from our laboratory has highlighted the role of both the hypothalamic NF-B (67,89,94,96) and TGF␤ (89) pathways in metabolic syndrome. Considering that mitochondrial dysfunction (90) and mtDNA (31) are known to trigger activation of the TGFß pathway, we studied levels of downstream signaling molecules including Smad and ERK1/2 via Western blot of hypothalamic tissues. Analysis of hypothalamic proteins revealed that a single hypothalamic infusion of mtDNA increased levels of phosphorylated Smad2 and ERK1/2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%